Prologue to Symposium on Multiple Pregnancy - Pacheco-Romero, José (2015)
National Daniel Alcides Carrión of Callao, Peru, Hospital recently organized under the leadership of Dr. Rommel Lacunza a symposium on multiple pregnancy, a little-revised, but which is has existed throughout the ages, something else in the 3-4 decades (1). Some years ago, Hellin postulated that twin pregnancy occurred in the proportion of 1 in 89 births, and triple, quadruple and higher order pregnancies appeared in the 1 in 892, 1: 893, 1: 89N (2). In England and Wales, the incidence of multiple pregnancies increased from 10 per 1000 in 1980 to 16 per 1000 in 2009, indicating an important cause the success of assisted reproduction techniques and the occurrence of multiple pregnancies up to 24% Where in vitro fertilization (1) was used. In a Peruvian study, the incidence of multiple pregnancy was 1.1% in 314,078 newborns, increasing to 2.7% when associated with preeclampsia (3). In the Latin American Network of Assisted Reproduction, in its report of 2012, the rate of multiple births was 30.2% (27.8% and 2.4% doubles triples and above) in 47,326 procedures (4).